PENGARUH EXCHANGE RATE, TUNNELING INCENTIVE DAN TAX PLANNING TERHADAP KEPUTUSAN TRANSFER PRICING (STUDI DI BEBERAPA SEKTOR PADA BURSA EFEK INDONESIA 2017-2019) - Widiana, I Gusti A.E; Sondakh, Jullie j.; Wangkar, Anneke (Universitas Sam Ratulangi, 2021)
Globalization makes national barriers no longer visible. Many companies are moving their companies to Indonesia as a result of globalization. When a company establishes a company in Indonesia, the company must pay taxes. Taxes are a burden for companies, so companies tend to avoid taxes through transfer pricing. Many factors influence transfer pricing decisions. These factors are exchange rate, tunneling incentive, and tax planning. This study aims to determine the effect of exchange rate, tunneling incentive, and tax planning on transfer pricing decisions. The analytical method used in this research is a quantitative analysis technique method with multiple regression analysis which aims to see the effect of the independent variable on the dependent variable and the type of research used is descriptive quantitative. The results of the study show that the exchange rate has no effect on transfer pricing decisions, tunneling incentive and tax planning have effect on transfer pricing decisions.